Pemberdayaan Ibu PKK Untuk Mewujudkan Keluarga Sehat dan Berkualitas di Panggungharjo Sewon, Bantul, Yogyakarta - Hindriyawati, Wiwin; Revika, Era; Cahya Ningsih, Rihul Aula; Haba, Valentesa Dwiyanti; Ariani, Thania (The Journal of Innovation in Community Empowerment, 2024)
Clean and healthy living behavior is a form of daily behavior that is very important to carry out because it supports the creation of a better quality of life. Balanced Nutrition is a reference for someone to consume nutrients according to the body's needs so that they can prevent various nutritional problems. Objectives: Increase the knowledge of PKK mothers about the importance of clean and healthy living behavior, can change their lifestyle to be cleaner and healthier, Learn the importance of fulfilling balanced nutrition. Method: The method used in this community service is counseling and movie learning to 29 female PKK in Panggangharjo District. Results: In this service, the results obtained were that the knowledge of female PKK increased as seen from the pretest and posttest scores. It is known that the percentage of pre-test results who lack knowledge about clean and healthy living behavior and balanced nutrition is 31%. At the time of counseling, the post test results were 0%. Then for the pretest results with sufficient knowledge, the results were 52%, dropping to 31%. Meanwhile, the pretest results of participants from 17% experienced an increase in knowledge which was visible from the posttest results to 69% with the results of participants' knowledge becoming better.